(untitled) (Journal of the College of Basic Education, 2025)
The current study aimed to identify self-regulated learning and its relationship to information generation skills among students in the Department of Islamic Education, College of Basic Education, Al-Mustansir Iya University. The study sample consisted of (65) male and female students from the Department of Islamic Education. To achieve the study objectives, the researcher used a self-regulated learning questionnaire based on Zimmerman’s theory (1989-2006). The scale consisted of (40) items. She also constructed a questionnaire for information generation skills, consisting of (15) items. The researcher constructed both of these items, which were both valid and reliable. The reliability of the scale using Cronbach’s alpha method reached (73%, 78%), which is considered a good reliability coefficient when compared to previous studies and research. The results showed that third-year Islamic Education Department students for the 2024-2025 academic year had a high level of self-regulated learning and information generation skills. There were no statistically significant differences between self-regulated learning and information generation skills. Based on these findings, the researcher made several recommendations, including: Incorporating self-regulated learning skills into educational curricula from the early stages of education. The need to reconsider traditional teaching methods and shift toward information generation skills.